The predictive role of support in the birth experience: A longitudinal cohort study. Issue 6 (December 2017) - Sigurdardottir, Valgerdur Lisa; Gamble, Jennifer; Gudmundsdottir, Berglind; Kristjansdottir, Hildur; Sveinsdottir, Herdis; Gottfredsdottir, Helga
Abstract: Background: Several risk factors for negative birth experience have been identified, but little is known regarding the influence of social and midwifery support on the birth experience over time. Objective: The aim of this study was to describe women's birth experience up to two years after birth and to detect the predictive role of satisfaction with social and midwifery support in the birth experience. Method: A longitudinal cohort study was conducted with a convenience sample of pregnant women from 26 community health care centres. Data was gathered using questionnaires at 11–16 weeks of pregnancy (T1, n = 1111), at five to six months (T2, n = 765), and at 18–24 months after birth (T3, n = 657). Data about sociodemographic factors, reproductive history, birth outcomes, social and midwifery support, depressive symptoms, and birth experience were collected. The predictive role of midwifery support in the birth experience was examined using binary logistic regression. Results: The prevalence of negative birth experience was 5% at T2 and 5.7% at T3. Women who were not satisfied with midwifery support during pregnancy and birth were more likely to have negative birth experience at T2 than women who were satisfied with midwifery support. Operative birth, perception of prolonged birth and being a student predicted negative birth experience at both T2 and T3. Conclusions: Perception of negative birth experience was relatively consistent during the study period and the role of support from midwives during pregnancy and birth had a significant impact on women's perception of birth experience.